The origin of citrus - Talón, Manuel; Wu, Guohong Albert; Gmitter Jr., Frederick G.; Rokhsar, Daniel S. (Elsevier, 2021)
In this chapter, we revise the origin of citrus and other related subjects such as their dispersal and evolution that have been a matter of controversy and have remained elusive during the past centuries. Comparative genomic analyses, however, have recently provided evidence that supports the proposal that the center of origin of citrus was the Southeast foothills of the Himalayas, in a region including the eastern area of Assam, northern Myanmar, and western Yunnan. This new vision also suggests that citrus evolved during the Late Miocene through a rapid Southeast Asian radiation correlating with a dramatic weakening of the monsoons provoked by a period of global cooling. The Australian limes and the Japanese Tachibana mandarin split later from mainland citrus during the Early Pliocene and Pleistocene, respectively. Taken together, these findings draw a new evolutionary framework for these fruit crops, a scenario that challenges current taxonomic and phylogenetic thoughts and points toward a reformulation of the genus Citrus.